Trifluorodiazoethane: A versatile building block to access trifluoromethylated heterocycles - Kumar, Anuj; Khan, Waqas Ahmad; Ahamad, Shakir; Mohanan, Kishor (Journal of heterocyclic chemistry, 2022)
Trifluoromethylated heterocycles have attracted remarkable interest in the last decades. The beneficial physicochemical and biological properties imparted by the incorporation of trifluoromethyl group into heterocycles have been the key factors to the frequent occurrence of trifluoromethyl group in several heterocycles of pharmaceutical and agrochemical relevance. In consequence, the construction of this class of compounds has become a major subject of research in recent years. In this context, 2,2,2‐trifluorodiazoethane (CF3CHN2) has emerged as an important reagent in the synthesis of trifluoromethylated heterocycles, thanks to the versatility of this reagent in undergoing a multitude of synthetic transformations. CF3CHN2 readily participates in [2 + 1]‐, [3 + 2]‐, and [3 + 3]‐cycloaddition reactions, as a trifluoromethyl‐containing dipole, thereby creating new approaches to trifluoromethylated heterocycles. The last decade has witnessed phenomenal growth in this area, and now, several methods are available to access highly functionalized 5‐ and 6‐membered trifluoromethyl‐containing heterocycles. In this review, we aim to demonstrate the use of CF3CHN2 in the preparation of different classes of CF3‐substituted heterocycles, giving emphasis to the past 10 years. This account details the recent advances in exploring the synthetic utility of trifluorodiazoethane for the construction of trifluoromethylated heterocycles.